ANALISIS KOGNITIF PESERTA PELATIHAN VOKASIONAL RENCANA USAHA DAN MANAJEMEN KEUANGAN KELOMPOK SWADAYA MASYARAKAT (KSM) BINAAN BDC SRIWIJAYA PALEMBANG - Thoyib, Ellys; Effendi, R.Y. (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
The purpose of the analysis is to find out the cognitions that appear in the cognitive system of vocational training participants in business plans and financial management of self-help groups (KSM) assisted by BDC Sriwijaya Palembang through the pre-test and post-test answers.There are 3 groups of knowledge behavior modes in participants' memories, namely positive mode 73%, negative 17% and doubtful 10%.Through the statement "I believe being able to understand the material of business plans and financial management" 83% positive and 17% negative cognitions are generated in the cognitive structure.These cognitions integrate with cognitive functions namely new cognitive notions, emotions, attitudes and motivations.New cognitive understanding results from integration with emotions, namely positive cognition 74% and negative 26%, a change in 9% positive cognition switches to negative.Integration of cognition with attitudes produces positive cognition 44%, negative 7% and neutral 49%, here there is a transition between positive and negative cognition to neutral cognition or no opinion at all. Integration with motivation by asking KSM motives / hopes, generated business capital assistance motives positive cognition 89% negative 11%, marketing assistance motives, 70% positive cognition 30%, and guiding motives to developing KSM efforts, positive cognition 92% negative 8%.Conclusion Changing habits that have been practiced for years will take time, energy and great breakthroughs about training methods that they are easy to understand.